The influence of integrating animation video media with critical incident strategy on Islamic studies learning outcomes - Dienana, Arina; Ramadhan, Aji Rizqi; Abdurrahman, Maman; Karimah, Sumayyah; Fauziyah, Widad Nur (TAWAZUN: Jurnal Pendidikan Islam, 2025)
This study aimed to find out how using animated video learning tools along with critical incident learning strategies affects the learning results of students at SDN Tunggul 1 Gondang, Sragen. The method used in this study is a quantitative experimental approach with a quasi-experimental design, specifically a nonequivalent group design. After testing the validity of the instruments, carrying out the implementation, and evaluating the process, the researcher collected test data for analysis. The data was found to be normally distributed and homogeneous in the prerequisite test. Then, the data was analyzed using the t-test (independent sample t-test). The results of the study showed an improvement in Arabic language learning outcomes when using animated video learning tools combined with critical incident learning strategies at SDN Tunggul 1 Gondang, Sragen. This was supported by the results of statistical tests, which showed a significance level (2-tailed) of 0.000 < 0.05, as tested using SPSS software. Therefore, it can be concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, meaning there is a difference in the Arabic language learning outcomes between the experimental class and the control class. Abstrak Tujuan dari penelitian ini untuk mengetahui pengaruh penerapan media pembelajaran video animasi digabungkan dengan strategi pembelajaran critical incident terhadap hasil belajar siswa SDN Tunggul 1 Gondang, Sragen. Pendekatan yang digunakan dalam penelitian ini ialah metode kuantitatif eksperimen dengan design penelitian quasi eksperimen berupa nonequivalent group design. Setelah melakukan validitas instrument, penerapan dan evaluasi, peneliti menerima data tes untuk dianalisa hingga diketahui bahwa data dalam penelitian ini berdistribusi normal dan bersifat homogen pada uji prasayarat. Selanjutnya data dianalisa menggunakan uji t (independent sample t test). Hasil penelitian menunjukkan adanya peningkatan hasil belajar bahasa Arab menggunakan media pembelajaran video animasi digabungkan dengan strategi pembelajaran critical incident terhadap hasil belajar siswa SDN Tunggul 1 Gondang, Sragen. Didukung dengan hasil uji statistic yang menunjukkan sig. (2-tailed) pada uji independent sample t test sebesar 0,000 < 0,05 yang diuji menggunakan perangkat lunak SPSS. Dengan demikian, dapat disimpulkan bahwa Ho ditolak dan Ha diterima, sehingga dapat dikatakan bahwa terdapat perbedaan hasil belajar mata pelajaran bahasa Arab kelas eksperimen dengan kelas kontrol.